The gut microbiota–brain–CAR T cell axis: a systematic review of gut microbiome modulation and its impact on neurological complications and treatment responses in CAR T cell therapy - Pillai, Ashvath Arumugam; Pasya, Sai K. Reddy; Kansal, Gaurav; Jaikrishnan, Aishwarya; Chauhan, Anchit; Das, Arghadip; Manojbhai, Korat Parth; Prabu, V. Deepak; Nashatizadeh, Muhammad Mahdi (Frontiers in Immunology, 2026)
BackgroundCAR T-cell therapy represents a substantial advance for relapsed/refractory hematologic cancers, but toxicities still limit its benefits. A particular concern is immune effector cell–associated neurotoxicity syndrome (ICANS), whose mechanisms remain only partly resolved. In parallel, work across immunology and neurogastroenterology shows that gut microbial communities can shape systemic inflammation and show correlations with brain function. Together, these strands suggest—without yet proving—that microbiome features could bear on both CAR T efficacy and ICANS risk.ObjectivesWe examined human clinical evidence at three touchpoints: how CAR T and the gut microbiota interact; how gut profiles relate to brain function; and which signals accompany CAR T–related neurotoxicity. The aim was to locate areas of overlap, not to claim a single causal chain.MethodsFollowing PRISMA, PubMed, Scopus, and Embase were searched from 2015 to 11 April 2025. We included randomized trials, prospective cohorts, and retrospective series reporting gut microbial composition, inflammatory or neurobiological markers, CAR T outcomes, or ICANS. Study quality was appraised with the Newcastle–Ottawa Scale and certainty graded with GRADE.ResultsTwenty-five studies were included (four CAR T–gut, eleven gut–brain, ten CAR T–neuro). Recurrent signals were (i) reduced microbial diversity, (ii) loss of short-chain fatty-acid producers, and (iii) prior antibiotic exposure—each linked to poorer clinical outcomes and higher or more severe ICANS. Candidate markers (e.g., C-reactive protein, interleukin-6, neurofilament light chain) and imaging findings, including PET abnormalities, were reported but remain exploratory and variably measured. Included studies are small and methodologically varied, and results should be interpreted with caution.ConclusionTaken together, the data support a convergence model: the gut microbiota may correlate with both treatment efficacy and neurotoxicity in CAR T recipients. The signal is consistent yet preliminary. Microbiome interventions such as probiotics and FMT are investigational and not yet recommended for CAR T recipients. Prospective, mechanism-rich studies—ideally pairing longitudinal stool profiling with inflammatory panels and neuroimaging—are needed before clinical translation.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024548645